2016
DOI: 10.1152/ajpendo.00520.2015
|View full text |Cite
|
Sign up to set email alerts
|

Enteral β-hydroxy-β-methylbutyrate supplementation increases protein synthesis in skeletal muscle of neonatal pigs

Abstract: -Many low-birth weight infants are at risk for poor growth due to an inability to achieve adequate protein intake. Administration of the amino acid leucine stimulates protein synthesis in skeletal muscle of neonates. To determine the effects of enteral supplementation of the leucine metabolite ␤-hydroxy-␤-methylbutyrate (HMB) on protein synthesis and the regulation of translation initiation and degradation pathways, overnightfasted neonatal pigs were studied immediately (F) or fed one of five diets for 24 h: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 83 publications
(124 reference statements)
1
35
1
Order By: Relevance
“…Moreover, intravenous infusion of HMB with increasing doses in neonatal piglets for one hour leads to mTOR activation and an increase in muscle protein synthesis [ 65 ]. HMB supplementation also increased skeletal muscle protein anabolism in neonates by stimulation of protein synthesis and satellite cell proliferation [ 66 ]. A novel study reported that HMB enhances the gain of skeletal muscle mass by increasing protein synthesis or/and attenuating protein degradation, and improves protein anabolism in muscles by increasing phosphorylation of protein anabolic molecules [ 67 ].…”
Section: Roles Of Bcaas In Nutrition Metabolismmentioning
confidence: 99%
“…Moreover, intravenous infusion of HMB with increasing doses in neonatal piglets for one hour leads to mTOR activation and an increase in muscle protein synthesis [ 65 ]. HMB supplementation also increased skeletal muscle protein anabolism in neonates by stimulation of protein synthesis and satellite cell proliferation [ 66 ]. A novel study reported that HMB enhances the gain of skeletal muscle mass by increasing protein synthesis or/and attenuating protein degradation, and improves protein anabolism in muscles by increasing phosphorylation of protein anabolic molecules [ 67 ].…”
Section: Roles Of Bcaas In Nutrition Metabolismmentioning
confidence: 99%
“…This is 6 to 7-fold higher than the highest levels fed to newborn term pigs that increased fractional rates of protein synthesis in several tissues (80 μmol/kg-day [ 36 ]) and the 70 μmol/kg-day that increased growth of IUGR term pigs [ 19 ]. Although not measured in the present study, plasma HMB concentrations are reported as ~1/1000 of the enteral dose [ 36 ]. Although speculative, the HP+HMB pigs would potentially have plasma concentrations of ~400 nmol.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first described mechanisms of HMB action was the effect on muscle protein metabolism. Preliminary studies suggest that HMB protects the skeletal muscle by inhibiting protein degradation ( 5 ) and by stimulating protein synthesis ( 6 ) ; however, this issue is subjected to constant research ( 17 ) . Functional analyses have demonstrated significant DEG enrichment of terms associated with cellular protein maintenance (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In adult skeletal muscle, regeneration and hypertrophy depend on the activation of mononucleated, muscle precursor cells called satellite cells (SC) ( 15 ) , embedded between the sarcolemma and the basement membrane of muscle fibres. Previous in vitro and in vivo studies indicate that HMB may activate SC ( 8 , 10 , 16 , 17 ) , but the mechanism underlying this action remains unclear. Some evidence suggests that HMB regulates the expression of myogenesis-related genes ( 8 ) ; however, until now, no one has demonstrated any effect of HMB on global gene expression.…”
mentioning
confidence: 99%